Immortal Time Bias in Cohort Studies: A Concept Simply Explained - Chittaranjan Andrade (Indian Journal of Psychological Medicine)
Immortal time bias is one of many types of bias that may flaw cohort studies. This bias occurs when formal observation of patients starts before they experience the exposure of interest, and when, by design, those who experience the outcome of interest before they experience the exposure are ineligible to be included in the exposure arm of the study. Consequently, patients in the exposure arm, by design, are immortal to the outcome between the start of observation and point of the exposure. If this period of immortality is included in analysis, the result is immortal time bias. This concept is explained with one hypothetical example, related to selective serotonin reuptake inhibitor exposure and prevention of ischemic heart disease events, and one published example, related to the use of suvorexant to prevent delirium during intensive care unit admission. Also explained is how immortal time bias can be avoided, and why an awareness of the concept is important when reading studies that employ observational designs.